PENGARUH ELECTRONIC WORD OF MOUTH DAN PERCEIVED BRAND INTERACTIVITY TERHADAP KEPUTUSAN PEMBELIAN DENGAN KEPERCAYAAN SEBAGAI VARIABEL INTERVENING (Studi pada Konsumen Produk Somethinc di Wilayah Jawa Tengah) - Farah Alifia; Farida Indriani (Faculty of Economics and Business Diponegoro University, 2022)
The facial care and cosmetic industry in Indonesia continue to increase during the Covid-19 pandemic whereas many other industries are affected and encountered a decrease. Thus made this topic an interesting topic to research. This study was conducted to determine the effect of electronic word of mouth and perceived brand interactivity on purchase decisions by using source trustworthiness as an intervening variable on a local skincare brand from Indonesia, namely Somethinc. Samples were taken from product users who are social media followers of the Somethinc brand and domiciled in the Central Java region. The analytical technique used in this study is the structural equation model (SEM) using AMOS 24.0 as an analytical tool. There are five hypotheses proposed in this study, and the results of data processing show that the five hypotheses were successfully accepted. Electronic word of mouth has been shown to have a positive and significant effect on source trustworthiness, perceived brand interactivity also has a positive and significant influence on source trustworthiness, while source trustworthiness has a significant positive effect on purchase decisions, and electronic word of mouth and perceived brand interactivity have a significant positive effect to the purchase decision.